If you can’t be here, be here. Modes and strategies of online protest of the Black Lives Matter movement - Vannoni, Mirco (E|C, 2021)
Eight minutes and forty-six seconds. This is the time in which the murder of George Floyd, in Minnesota, took place on 25 May 2020. A further act of institutionalized violence – granted, legitimized and overlooked by institutions – that made necessary for the Black Lives Matter (BLM) movement to start a series of protests to draw attention to the abuse of power of a racist and corrupt system that highlights the breakdown of the social pact between people in a society. Beyond the ethical and political significance of the event, our contribution aims to reflect on the forms of occupation of the physical and virtual spaces through which BLM constitutes itself as a movement and organizes conflict. The analysis will focus on two fundamental aspects of the protest that are closely linked to the sense of space. The first concerns the way BLM fits into the lockdown condition imposed by the pandemic and tactically exploits the different spatial relationship that it imposes on the inhabitants of the planet, globally immobilized as physical bodies and hyper-exposed to the digital world. On the one hand, street demonstrations amplify the sense of resistance and dissent expressed by the mere fact of finding and moving together through public space at a time when everyone is ordered to stay at home. On the other hand, when protests and actions are organized trough digital media, they do not limit to individual complaints or petitions, but involve meetings and discussions on different platforms. Discussions range from political and cultural debate to the organization of the protest, coordinating collective actions such as “If You Can’t Be Here, Be Here”, implemented by LDNBLM.